Volume 9A: Ocean Renewable Energy 2014
DOI: 10.1115/omae2014-23406
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mudline Damping for Offshore Wind Turbine Monopiles

Abstract: Fatigue is often a design driver for large (e.g. 5–10 MW) offshore wind turbines (OWTs), necessitating a thorough examination of damping sources: aerodynamic, hydrodynamic, structural, and soil. Of these sources, soil damping has been least considered by researchers with respect to OWTs. Aeroelastic programs, such as the National Renewable Energy Laboratory (NREL) code FAST, are typically used for time history analysis of aerodynamic and hydrodynamic loads experienced by OWTs. To take into account foundation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The viscous dampers have been calibrated to give a foundation damping factor of approximately 1 % near rated wind speed conditions (load case 6). This is considered reasonable and in line with studies from literature (Shirzadeh et al, 2013;Carswell et al, 2014). The foundation damping factor of 1 % expresses the hysteretic energy loss in the soil as a percentage of the total elastic strain energy of the soil.…”
Section: Calibration Of Modelsupporting
confidence: 59%
“…The viscous dampers have been calibrated to give a foundation damping factor of approximately 1 % near rated wind speed conditions (load case 6). This is considered reasonable and in line with studies from literature (Shirzadeh et al, 2013;Carswell et al, 2014). The foundation damping factor of 1 % expresses the hysteretic energy loss in the soil as a percentage of the total elastic strain energy of the soil.…”
Section: Calibration Of Modelsupporting
confidence: 59%
“…A number of studies have been carried out to fill this gap, in most cases by performing emergency OWT shut-downs, i.e. rotor-stop tests (Tarp-Johansen et al, 2009;Versteijlen et al, 2011;Damgaard et al, 2012Damgaard et al, , 2013Shirzadeh et al, 2013;Carswell et al, 2014). Table 4 provides a synopsis of methodologies and inferences from the cited literature studies, as well as a solid ground to assess this study's results -extracted from the most meaningful cases D r = 60-80%.…”
Section: Owt Dampingmentioning
confidence: 99%
“…They found that a 50 % reduction in the soil's Young modulus increased the fatigue damage equivalent moment at mud-line by approximately 12 %; and a 50 % reduction of the soil damping properties increased the fatigue damage equivalent moment by 25 %. Carswell et al (2015) studied the effect of soil damping for an OWT with a monopile foundation subjected to extreme storm loading. The hysteretic damping was computed using a non-linear elastic two-dimensional finite element model and was included in the foundation model by a viscous rotational damper at mud-line.…”
Section: Numerical Studies Investigating Effects Of Soil Stiffness Anmentioning
confidence: 99%
“…5, where K is a stiffness matrix, d is a displacement vector, and C is a damping matrix. In Model 3, damping coefficients are only applied in rotational degrees of freedom (rotation around x and y axes), as moments typically dominate mud-line loading for OWT monopiles (Carswell et al, 2015). The moment response for a single degree of freedom is given by…”
Section: Modelmentioning
confidence: 99%